ANALISIS PENGARUH DUKUNGAN ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP ORGANIZATIONAL CITIZENSIP BEHAVIOR DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PDAM TIRTA MOEDAL KOTA SEMARANG) - Wulandari, Ambar Dwi; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2017)
In the service industry, employee who performs direct contact with consumers is representatives ofÂ organization service quality. PDAM Tirta Moedal as one of organization which prioritize the quality of service, that became the center of water services for the entire community of Semarang City requires employees who provide more performance / extra job-role or so-called OCB behavior in order to be able to serve the people of Semarang city optimally. This research was conducted by indication that OCB level of PDAM Tirta Moedal was still low that reflected by employee attendance, employees attendace is used as indicator that measures on of OCB dimensions which is conscientiousness dimension.The purpose of this study was to examine the effect of perception of organizational support and career development on organizational citizenship behavior with employee engagement role as intervening variable. This research was conducted at PDAM Tirta Moedal Semarang. The sample size was 74 respondents with sampling technique using proportionate stratified random sampling. The analysis used included multiple linear regression analysis, path analysis (Path Analysis) and test of sobel to test mediation effect.The results show a positive and significant relationship between (a) organizational support with employee engagement, (b) career development with employee engagement, (c) organizational support with OCB, (d) career development with OCB, (e) employee engagement with OCB . The results of this study also show that employee engagement proved to be a mediating variable between organizational support and career development towards OCB.